Evidence-based health informatics promoting safety and efficiency through scientific methods and ethical policy - Ammenwerth, Elske 1970-; Rigby, Michael (Studies in health technology and informatics, 2016)
"Health IT is a major field of investment in support of healthcare delivery, but patients and professionals tend to have systems imposed upon them by organizational policy or as a result of even higher policy decision. And, while many health IT systems are efficient and welcomed by their users, and are essential to modern healthcare, this is not the case for all. Unfortunately, some systems cause user frustration